Contextual aspects and environmentally ethical behaviour: a review - Mashitoh Yaacob (Environmental Management Society, Malaysia, 2007)
A comprehensive review of literature indicates varying hypotheses of the relationship between contextual aspects (i.e., social, economic, and political) and environmentally ethical behaviour (EEB) (i.e., pre-cycling, re-use and recycling). This article divides the discussion into four thematic categories (i.e., social intrinsic aspect, social extrinsic aspect, economic aspect, and political aspect). In each of the categories this article provides a comprehensive review of the research findings. From the literature reviewed, it can be said that a study on the relationship between social intrinsic aspect and EEB is a study about environmental attitude in relation to environmental behaviour. Findings of the studies on such relationship are inconsistent; some found a positive relationship and some show a weak or no relationship. However, most of the studies found that general environmental concern were not strongly related to a specific EEB whereas specific environmental attitudes and/or beliefs (e.g., locus of control), and personal psychological features (e.g., social conscience) linked positively to EEB. Meanwhile, some elements of social extrinsic aspect (e.g., social pressure from neighbours) were found to relate strongly (directly or indirectly) to EEB. Others (e.g., personal convenience) were found to either have no relationship or have a negative relationship to EEB. On the relationship between economic aspect and EEB, some studies found financial incentives correlate positively to EEB, but others found that such incentives were not effective in the long run. Some elements of economic aspect (e.g., price) linked negatively to EEB while product attributes linked positively. As for political aspect and its relation to EEB, variables such as laws and regulations had a weak relation with EEB, but environmental NGOs had a strong relation with EEB